Handbook of research on small and medium enterprises in developing countries - Ahmad, Noor Hazlina, 1974-; Ramayah, T., 1964-; Halim, Hasliza Abdul, 1975- (IGI Global, 2017)
"This book provides broad research and applied coverage of subjects on all areas of small medium entrepreneurship and its implications in developing countries. This book aims to explore the opportunities and challenges confronting small medium enterprises in the developing countries and outline possible avenues for the growth of this sector"--Resumé vydavatele
Keywords: malé a střední podniky; informační technologie; podnikání; small and medium-sized enterprises; information technology; business; příručky; elektronické knihy; handbooks and manuals; electronic books